2014
DOI: 10.1063/1.4881675
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory motion of water droplets in kerosene above co-planar electrodes in microfluidic chips

Abstract: We experimentally observed oscillatory motion of water droplets in microfluidic systems with coplanar microelectrodes under imposed DC electric fields. Two-electrode arrangement with no bipolar electrode and eight-electrode arrangement with six bipolar microelectrodes were investigated. Kerosene was used as the continuous phase. We studied the dependences of the oscillation frequency on the electric field intensity and ionic strength of the water phase. We found that the electric field dependence is strongly n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…Analysis of the recorded video to determine the corresponding acquired charge (by balancing the electrostatic force versus the drag force) indicates that the metal ball typically receives about 70 pC to 250 pC of charge from either electrode depending on the applied field strength, while the droplet receives approximately 110 and 200 pC from the negatively and positively charged electrode respectively. The overall behavior of the droplets and metal balls, including the magnitude of charge acquired, is broadly consistent with previous studies [9,14,18,19,24]. Examination of 50-nm thick electrodes after electrically bouncing a water droplet reveals no changes visible to the naked eye.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…Analysis of the recorded video to determine the corresponding acquired charge (by balancing the electrostatic force versus the drag force) indicates that the metal ball typically receives about 70 pC to 250 pC of charge from either electrode depending on the applied field strength, while the droplet receives approximately 110 and 200 pC from the negatively and positively charged electrode respectively. The overall behavior of the droplets and metal balls, including the magnitude of charge acquired, is broadly consistent with previous studies [9,14,18,19,24]. Examination of 50-nm thick electrodes after electrically bouncing a water droplet reveals no changes visible to the naked eye.…”
supporting
confidence: 73%
“…Although similar light flashes have been previously observed when charged objects [13,14] or liquid drops [26] approached an electrode, recent workers have assumed that electrically bouncing droplets are charged via electrochemical reactions not involving dielectric breakdown [18,19]. It is known from previous work that application of an arc current on the order of 1-100 amps between stationary electrodes through vacuum can melt the electrodes via Joule heating, with the high pressure present in the plasma jet of the arc pushing the molten material to form micron-scale craters [27,28].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This approach has been applied previously in some models. For example, Bernanek et al 54 used the exchanged charge value as a free parameter to adopt their model predictions with the experimental data. Figure 16 indicates that the reduction of the particle charge in downward motion can significantly retard the particle downward trajectory.…”
Section: Comparison With Experimental Data and Discussionmentioning
confidence: 99%
“…3 Numerous studies [3][4][5][6][7][8][9][10][11][12][13] have reported various modes of droplet motion between electrodes using both experimental and numerical methods. A droplet behaves as an electrical charge-carrier between a pair of electrodes in an oil medium as an insulator.…”
Section: Introductionmentioning
confidence: 99%